PLANEACIÓN FINANCIERA A LA EMPRESA FARMAMIA CÍA LTDA DE LA CIUDAD DE MACHALA, PROVINCIA EL ORO, PERÍODO 2018 - 2022 - Ochoa Chamba, Ana Cristina (2019)
This thesis work entitled "FINANCIAL PLANNING TO THE COMPANY FARMAMIA CÍA LTDA OF THE CITY OF MACHALA, PROVINCE EL ORO, PERIOD 2018 - 2022", was developed with the purpose of implementing the use of a financial tool such as, Planning Financial, according to the economic activities performed daily by the company, which will provide a significant contribution to the administrative staff of the company. To comply with the specific objectives, it began with the collection of information and financial statements of the year 2017 of the company, which allows to know what its economic - financial situation is. A prognosis of purchases and sales was developed, in order to know future economic results, which allows to make the most of the opportunities, using as base information the sales and historical purchases of the year 2017 and the month of December 2016, applying the percentage method of sales that determined the monthly increase, allowing to know, that the months of February, April, August and December are of greater income for the company. Then a cash budget was made to forecast future inflows and outflows of money, and prevent future situations, for the preparation of the same, the 5 cash inflow and outflow programs were considered, applying the percentage of increase in income and expenses, also took into account the sales and prognostic purchases for the calculation of cash programs. The cash outflow considered, in addition to the aforementioned, the wages and salaries of 2017, 2018 and 2019 for the calculation of the percentages of salary increases and other social benefits. Subsequently, the proforma Statement of Income and Financial Position was prepared in order to know the expected revenues, costs and expenses for subsequent years, increasing according to the volume of sales forecast; Finally, the Balance Point of the projected years was developed, which allowed determining the profitability that the company will obtain in the future. Finally, the conclusions and recommendations that are written based on the results obtained are described, therefore it is concluded that the company Farmamia Cía Ltda does not have a financial planning, cash budget, sales forecast, as well as sales and collection policies, what causes that the current and future financial situation cannot be known for the taking of corrective measures that allow to increase the economic and financial profitability.